Process Optimization and Quantification using BPM - Tocto Cano, Esteban (2011)
It’s shown a proposal for Optimization and Counting Processes using BPM tools (Business Process Management) at the university sphere. The process of Pre Pro- fessional Practice Management (PGPP) of the Universidad Peruana Union was optimized and automated, a subsidiary in Tarapoto (UPeU FT). The development of the design is based on interviews conducted at the operational level as the headmaster’s; the process optimization was performed using a tool for BPM mo- deling. The tool has different instruments which allow you to redefine processes, sub processes, tasks, deliverables, roles, responsibilities. In terms of measuring the effectiveness of the proposed process, it was implemented at the solution series of Key Performance Indicators (KPI’s) that allowed the effectiveness measu- rement of the solution set. The quantitative approach, definition and work with the indicators were defined according to different principles in the methodology of BPM.